2015
DOI: 10.7202/1028113ar
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Career Anchor Model: A Proposition and an Empirical Investigation of a New Model of Career Value Structure

Abstract: This study proposes an original model of career values organized in a circular logic. The new career value structure consists of four quadrants opposed in pairs (bureaucratic self-concept versus protean self-concept, and careerist self-concept versus social self-concept). Contrary to Schein’s model, which rests on the dominance of a single career anchor, our model organizes career anchors according to attraction and repulsion, which may explain the existence of several domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…Following this approach, the CVS is a circular model based on the correspondence between the four quadrants, 10 aforementioned motivational domains, and Schein's CAs, as follows: technical/functional competence and service/dedication to a cause are located in the self -transcendence quadrant; lifestyle and organizational security are located in the conservation quadrant; managerial competence and identity are located in the self-enhancement quadrant; and pure challenge, entrepreneurial creativity, and autonomy are located in the openness to change quadrant. Wils et al (2010Wils et al ( , 2014 concluded that several CAs are complementary (e.g., creativity and challenge), whereas others are conflictual (e.g., challenge and security). Conversely, the axis's correlation analysis indicates that each quadrant is negatively correlated with the others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this approach, the CVS is a circular model based on the correspondence between the four quadrants, 10 aforementioned motivational domains, and Schein's CAs, as follows: technical/functional competence and service/dedication to a cause are located in the self -transcendence quadrant; lifestyle and organizational security are located in the conservation quadrant; managerial competence and identity are located in the self-enhancement quadrant; and pure challenge, entrepreneurial creativity, and autonomy are located in the openness to change quadrant. Wils et al (2010Wils et al ( , 2014 concluded that several CAs are complementary (e.g., creativity and challenge), whereas others are conflictual (e.g., challenge and security). Conversely, the axis's correlation analysis indicates that each quadrant is negatively correlated with the others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More than 20 years after Schein's seminal studies, Feldman and Bolino (1996) mentioned that the model has made several contributions, such as it can predict individuals' career path choices, among other remarkable findings. Despite of this, the model also has been widely criticized, providing empirical evidence on the existence of individuals' multiple career paths (Chapman and Brown 2014), mutually exclusive and complementary career paths (Feldman andBolino 1996, Chapman andBrown 2014) and incompleteness in terms of inclusion of values and motivational domains (Wils et al 2010(Wils et al , 2014. Furthermore, COI literature has lacked of empirical studies using exploratory and confirmatory factor analysis in developing countries and detailed open access data for replicability and further meta-studies (Barclay et al 2013, Open Science Collaboration 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, the octagonal complementary/exclusion model proposed by Feldman and Bolino (1996) proved to be too limiting because some CAs' relationships were misrepresented and others were not represented at all (Barclay et al 2013, Chapman and Brown 2014, Roger 2006. To address this theoretical gap, Wils et al (2010Wils et al ( , 2014, by means of Guttman-Lingoes smallest space analysis applied to a sample of 880 engineers, proposed an original model for the COI based on Schwartz's universal values structure (UVS) (Schwartz and Boehnke 2004) called the career value structure (CVS). The UVS is a circular model intersected by two axes distributed to four quadrants and divided into 10 motivational domains.…”
Section: Introductionmentioning
confidence: 99%
“…Following this approach, the CVS is a circular model based on the correspondence between the four quadrants, 10 aforementioned motivational domains, and Schein's CAs, as follows: technical/functional competence and service/dedication to a cause are located in the self-transcendence quadrant; lifestyle and organizational security are located in the conservation quadrant; managerial competence and identity are located in the selfenhancement quadrant; and pure challenge, entrepreneurial creativity, and autonomy are located in the openness to change quadrant. Wils et al (2010Wils et al ( , 2014 concluded that several CAs are complementary (e.g., creativity and challenge), whereas others are conflictual (e.g., challenge and security). Conversely, the axis's correlation analysis indicates that each quadrant is negatively correlated with the others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation